The Effect of Ecoenzimes of Various Fruit Peel Waste on Decreasing Surfactant Concentration in Laundry Wastewater - Wahyu Safira Wulandari; Winarsih, Winarsih (LenteraBio : Berkala Ilmiah Biologi, 2023)
Laundry waste that is waste can pollute the environment and have a negative impact on humans. Detergent is a cleaning product that is commonly used in laundry process, which one of ingredients it is surfactant. Excessive surfactant can cause low oxygen absorption on waters and can reduce the ability of aquatic biota to reproduce. The one solution to reduce surfactant levels in laundry wastewater is to utilize organic waste, which was developed into ecoenzymes. This study aims to determine the characteristics of the resulting coenzymes and their effect on reducing surfactant levels in laundry wastewater. This study was an experimental study used a randomized block design (RBD) with the studied variable being the ecoenzymes concentration. Variations of ecoenzymes used were concentrations of 0%, 1%, 3%, 5% and 7% with a contact time of 5 days. Parameters tested included were surfactants, pH, TSS, and BOD5. Data analysis was performed used one way ANOVA followed by Duncan’s test to determine the best treatment for reducing surfactant levels. The results showed that the treatment of various ecoenzyme concentrations affected the decrease in surfactant levels in laundry wastewater. Treatment with a concentration of 5% had the highest percentage of reduction in surfactant content, namely 98.33% with a value of 2.94 mg/L on the fifth day.